Africa and Global Logistics as seen through the Networks of Container Shipping Companies - (:unkn) unknown (My University, 2017)
Studies on global shipping network show mainly the very relative weight of Africa in the world and the growing impact of Asia in Africa’s connectivity, at the expense of Europe. However, this global view overlooks the role of the international transportation stakeholders, especially the one of ship-owners, in the insertion of Africa in global flows. The combination of recent and original data about containerships moves with quantitative methods through network analysis and a more qualitative work on stakeholders’ strategies, allows identifying differentiated logics for the ship-owners and the uniqueness of the situation of Africa and its regions in the global shipping network.
Keywords: African Research